DISPARITAS PUTUSAN HAKIM DALAM PERKARA KORUPSI: ANALISIS TERHADAP FAKTOR-FAKTOR NON-YURIDIS - Leonardo Pratama (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2026)
Corruption is an extraordinary crime that damages the economic and social foundations of a nation. However, judicial practice often shows significant sentencing disparities in corruption cases with similar modus operandi and state losses. This study analyzes non-juridical factors causing judicial disparities in corruption cases in Indonesia using normative-juridical approach through court decision analysis and literature review. Results indicate that besides juridical factors, significant non-juridical factors include: judges' personal background and values, social and political pressure, public issues and media coverage, and organizational culture within judicial panels. Sentencing disparities reflect not only legal failures but also human factors and social contexts in decision-making processes. Systematic efforts are needed including continuous judicial training, integrity strengthening, better judicial transparency, and socialization of sentencing guidelines.